The plural society and the problem of order - Bekker, Simon (Department of Sociology, 2016)
Pluralism, as a sociological perspective to study multi-ethnic and multi-racial societies, is a popular and well-known approach. It is also an approach which has been repeatedly and effectively criticized. This study focuses upon pluralism and the problem of order in society. Hereby, a new pluralist perspective is developed which avoids the pitfalls of the traditional approach, on the one hand, and yet retains the valid emphasis on pluralism, on the other. By applying this new perspective, it is possible to analyze the changing relationships he tween the cultural (and racial) characteristics in the society, and its structural characteristics. In this way, it is hoped, more may be learnt about the nature of a plural society and about the ways it can change.